Recent advances in liver transplantation with HCV seropositive donors - Murag, Soumya (F1000Res, 2019)
The paradigm shift from interferon-based to direct-acting antiviral (DAA) therapy for the treatment of hepatitis C virus (HCV) infection has revolutionized the field of liver transplantation. These advances in effective HCV treatment, along with the persistent shortage in available liver grafts, have encouraged investigators to assess the need for adopting more inclusive donor policies. Owing to the poor outcomes following liver transplantation with recurrent HCV infection, liver transplantation using HCV seropositive donors (non-viremic and viremic) had been restricted. However, as a result of the growing supply of HCV seropositive donors from the recent opioid epidemic along with the advent of efficacious DAA therapy to treat HCV recurrence, there has been an increasing trend to use HCV seropositive donors for both HCV seropositive and seronegative recipients. The review aims to discuss recent advances and associated outcomes related to the use of HCV seropositive grafts for liver transplantation.